2012
DOI: 10.4236/jbise.2012.56038
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots induce hot-start effects for Taq-based polymerase chain reaction

Abstract: Decent hot-start effects were here reported in Taq DNA polymerase-based polymerase chain reaction (PCR) when water-soluble CdTe quantum dots (QDs) were employed. The hot-start effects were revealed by the higher amplicon yields and distinguished suppression of nonspecific amplification after pre-incubation of PCR mix with quantum dots between 30°C and 56°C. DNA targets were well amplified even after PCR mixture was pre-incubated 3 hr at 30°C or 1 hr at 50°C. Importantly, the effects of QDs nanoparticles could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…These results further illustrated that there was likely a direct interaction between Pfu and CdTe QDs at low temperatures as reported previously. [16,17] The QDs used in this study are CdTe nanocrystals with a size of about 3-4 nm. Previous study [16] suggested that CdTe QDs directly interacted with Taq polymerase and such interaction may improve the catalytic activity of the Taq enzyme.…”
Section: Hot-start Effect In Fast Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…These results further illustrated that there was likely a direct interaction between Pfu and CdTe QDs at low temperatures as reported previously. [16,17] The QDs used in this study are CdTe nanocrystals with a size of about 3-4 nm. Previous study [16] suggested that CdTe QDs directly interacted with Taq polymerase and such interaction may improve the catalytic activity of the Taq enzyme.…”
Section: Hot-start Effect In Fast Pcrmentioning
confidence: 99%
“…[16,17] The QDs used in this study are CdTe nanocrystals with a size of about 3-4 nm. Previous study [16] suggested that CdTe QDs directly interacted with Taq polymerase and such interaction may improve the catalytic activity of the Taq enzyme. However, such improvement was not as good as that in QD-facilitated PCR based on Pfu polymerase.…”
Section: Hot-start Effect In Fast Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, one could develop new technology that would unify both the gene and protein analyses in a single platform by virtue of single biofriendly signal-generating probe to achieve rapid staining techniques. This would allow easy access of rapid diagnostics by a large population at an affordable cost. , The efficiency of the PCR process has been improved through the usage of metal nanoparticles, quantum dots, carbon nanotubes, carbon nanoparticles, graphene, etc. The plasmonic , and luminescent nanomaterials are useful as diagnostic probes in PCR and array-based methods. However, because of high sensitivity and background-related issues, fluorometric techniques are preferred over colorimetric assays .…”
Section: Introductionmentioning
confidence: 99%